PROGRAM CSR KOMPAS GRAMEDIA GROUP DALAM MEMPERTAHANKAN CITRA PERUSAHAAN MELALUI GERAKAN LITERASI NUSANTARA #AKUBACA - Robbikal Muntaha Meliala; Rety Palupi; Ezrin Septalastiani (Yayasan Akrab Pekanbaru, 2018)
Based on survey from UNESCO in 2015 has shown the reading interest of Indonesian people just meet 0,001 percent or from 1000 peoples, only 1 people of Indonesian who active like to read. This problem also bring Indonesia in 2016 had been declared as 60th ranked from 61countries about the reading interest or in other words, Indonesia were in bottom two toward reading interest. Reading preference appears because of many factors, such as from environment, families, school, access and others. Thatâ€™s why, Kompas Gramedia Group as a mass media company initiative to create CSR Program â€œNusantara Literacy Movementâ€ #IamReading. This CSR program has variant sub activities such as Book ATM, Books Donation and Mobile Library where supported by Literacy Communities and PT Pos Indonesia. Research Methodology: Descriptive Qualitative by Observations, Interviews, Study of Literature and Documentation. Summary: CSR Program of Kompas Gramedia Group with named â€œGerakan Literasi Nusantaraâ€ succeed to keep good image of company and got positive responses.